Monitoring and Eco-Friendly Management of Coffee White Stem Borer, Xylotrechus quadripes Chevrolat (Coleoptera: Cerambycidae) in Coffea arabica - Parajuli, Kiran; Paudel, Manoj; Tiwari, Sundar (Agriculture Development Journal, 2025)
Coffee, the most widely consumed beverage and important cash crop, is cultivated in more than 70 countries in the world. Coffee white stem borer (CWSB) is one of the major problems in organic arabica coffee production in Nepal. Hence, a study was carried out for eco-friendly management of CWSB by understanding its habitat and ecology. Pest monitoring using CWSB lure in three different locations of Gulmi district showed that late May and early June was the peak emergence period of the beetles. Their population was significantly higher in coffee orchards without shade as compared to shaded coffee orchards. Effects of four different eco-friendly management practices namely red soil plus cow dung, Bordeaux paste, stem scrubbing plus 20% kerosene, stem scrubbing plus 30% neem oil was studied on pest population and plant health. Effect of those treatments on the number of adults, larvae, exit holes and cracks was studied. Stem scrubbing plus 30% neem oil reduced the number of adults, larvae and cracks by 90%, 95% and 31% respectively in late May and early June. Red soil plus cow dung was most effective against exit holes, reducing it by 91% compared to control.